OBSERVING THE PROCESS OF LEARNING TO READ THE QURAN AT ELEMENTARY SCHOOL - Muhammad Yusuf Ihsan; Udin Supriadi; Agus Fakhruddin (Auladuna: Jurnal Pendidikan Dasar Islam, 2023)
Abstract The educational issue of learning to read Qur'an is currently growing. The number of students who still cannot read Qur'an following the rules is the main problem. This study describes the learning process of reading Qur'an at Darul Hikam Elementary School Bandung. A qualitative approach with case study method was used in this research. Data were obtained through observation, interview, and document study. The results of the data were processed using data reduction, data display, and conclusion drawing. The research findings show that the learning process of reading Qur'an at Darul Hikam Elementary School used the Teacher-Centered Learning pattern and implemented various learning methods at each grade level. The learning results show that students can read Qur'an in the "Good" category. Therefore, designing the process of learning to read Qur’an in private and public schools is needed to be developed so that it has various learning processes and improves students' abilities.